KARNALI Paradigm in the Development Domain - Aidee, Narbir (International Journal of Multidisciplinary Approach Research and Science, 2023)
The KARNALI Paradigm is a systematic methodology for development in Nepal's Karnali Province, prioritizing community empowerment, participatory development, and sustainability. It involves assessing needs, mobilizing communities, and planning projects, securing resources, implementing initiatives, and evaluating progress to create an inclusive and effective model of development. The paradigm recognizes the multidimensional nature of development, targeting economic, social, cultural, human, environmental, political, and technological aspects. It aims to reduce inequality, eradicate poverty, and improve access to goods, services, and opportunities. Accountability is essential for transparent and equitable development outcomes. A holistic approach promotes transparency and accountability through systems, policies, effective knowledge implementation, resource management, continuous learning, innovation, and stakeholder collaboration. The KARNALI Paradigm offers a framework to implement these recommendations, fostering accountability and positive societal change. By adopting the paradigm and implementing these strategies, individuals and organizations in the development sector can achieve their goals and create meaningful impact in Karnali Province.